Unique Patterns of Circulating Extracellular Vesicles in Preterm Infants During Adaptation to Extra-Uterine Life - Murphy, Claire A; O'Reilly, Daniel; Weiss, Luisa; Madden, Stephen; Macleod, Hayley; Chevillier, Ana Le; Neary, Elaine; O'Loughlin, John; El-Khuffash, Afif; Kevane, Barry; NíAinle, Fionnuala; Zivny, Jan; et al. (Journal of extracellular vesicles, 2025)
There is growing interest in the role of extracellular vesicles (EVs) in neonatal pathology. This study aimed to characterise circulating EVs following preterm birth. This single-centre prospective observational study included cord and postnatal plasma from preterm (n = 101) and full-term infants (n = 66). EVs were analysed using nanoparticle tracking analysis, flow cytometry, proteomics and procoagulant activity assay. We found changes in the concentration, size, cellular origin and proteomic content of circulating EVs in preterm infants during perinatal adaptation. To understand if these changes were related to prematurity or normal adaptation to extrauterine life, they were also investigated in term infants. There was a dramatic increase in the concentration of small and large EVs on Day 3 in the preterm group; specific subsets of platelet (CD42b+ and CD62P+), endothelial (VEGFR2) and tissue factor EVs were elevated. Differentially expressed proteins relating to haemostasis, pulmonary physiology and immunity were identified between Day 1 and 3 in preterm infants. These changes have never previously been described in a large cohort of preterm infants and differ from healthy term infants. These findings have major implications for future neonatal EV studies, particularly the timing of sample collection. Further work is required to understand the clinical implications of this unique EV profile following preterm birth.
Keywords: vascular biology; proteomika; umbilical cord; fyziologická adaptace; těhotenství; mužské pohlaví; Prospective Studies; Infant, Newborn; Extracellular Vesicles; Proteomics; ženské pohlaví; novorozenec; Humans; prospektivní studie; Pregnancy; extracelulární vezikuly; Infant, Premature; haemorrhage; neonatal; Female; novorozenec nedonošený; lidé; Male; Adaptation, Physiological